You Too, Brutus? Betrayal Trauma between Scotomization and Self-Confrontation (Psychoanalytic Study on Modernist Selected Poems) - Al-Moosawi, Haider Ghazi (Journal of Ecohumanism, 2024)
“You, too” strikes deep roots in the human dealings, sometimes it tends to an impetus to boost, sometimes a curb to sink like a stone. The acts of betrayal take hold of specific aspects: it is done to take, usurp and confiscate, or rather it is done to gain. In so doing, the victim here suffers and then reverts into the caves of scotomization. The current paper is to shed light on certain samples to prove that no trauma could persist in the face of human endeavours to give birth to oneself. To trace such a hypothesis, the theory of scotomization is to be explicated in the view of human defense mechanism to shield his vulnerable ores and values. First there will be a literature review to survey the gap to bridge in such a scope, and then there will be a manifestation to the nexus between betrayal trauma and scotomization. The samples of the study pays much heed to the diversity of the reasons beyond betrayal : Tattoo of Muhammad Al-Maghut imparts the suppressed shouts of a man on the verge of losing his entire temper ; everything in dark he does for fear of being arrested , Muzaffar Al-Nawwab in his Jerusalem Is Arab Nationalism’s Bride come in parallel with Muhammad Al-Maghut`s in matter of metaphoric manipulation in the image of virginity and the last sample unveils the fact that all secrets are to flow in a moment of confrontation ; A Ritual to Read to Each Other by William Stafford believes that time is so essential to give leads to the hidden secrets . Here comes the schema of the paper; events, trauma, scotomization, self- realization self-confrontation and rebirth. In applying such an eclectic model to the samples, it is found that all the personas liberate themselves but with versatile maneuvers.